2014
DOI: 10.1590/s1516-35982014000800005
|View full text |Cite
|
Sign up to set email alerts
|

Early weaning and concentrate supplementation strategies for lamb production on Tifton-85 pasture

Abstract: -The influence of early weaning and concentrate supplementation strategies on sward characteristics, forage chemical composition and lamb productivity were evaluated in four production systems on Tifton-85 pasture: suckling lambs not supplemented until slaughter; suckling lambs supplemented with concentrate in creep feeding until slaughter; early-weaned lambs not supplemented until slaughter; and early-weaned lambs supplemented with concentrate until slaughter. Structural, morphological and productive characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Lighter weaning weight of lambs makes mating management of hoggets difficult ( Kenyon, Morel & Morris, 2004 ). Moreover, early weaning gives ewes a greater period to rest and recover their body condition ( Arnold, Wallace & Maller, 1979 ; Lee, Majluf & Gordon, 1991 ; Silva et al., 2014 ) which may be a good strategy to increase reproductive performance of ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Lighter weaning weight of lambs makes mating management of hoggets difficult ( Kenyon, Morel & Morris, 2004 ). Moreover, early weaning gives ewes a greater period to rest and recover their body condition ( Arnold, Wallace & Maller, 1979 ; Lee, Majluf & Gordon, 1991 ; Silva et al., 2014 ) which may be a good strategy to increase reproductive performance of ewes.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a performance difference between supplemented and control animals, concluding that the nutrients provided by the pasture and the lactating ewes were sufficient to keep lambs at performance levels equivalent to lambs supplemented at 1% LW. Subsequent studies (11,20,21) indicated that, in that type of pasture, lamb supplement must be above 2% LW to induce measurable differences vis-á-vis control animals.…”
Section: Grazing Sheep Management and Supplementation Weaning And Concentrate Supplementationmentioning
confidence: 99%
“…Therefore, this strategy allows an early return of ewes to cyclicity, reducing the interval between parturitions, and increasing the rate of lambs produced per ewe year -1 (Oliveira et al, 2014). When weaning is associated with concentrate supplementation offered after weaning, the main results obtained are increased individual performance (Souza et al, 2010;Geron, Mexia, Garcia, Silva, & Zeoula, 2012) and lamb stocking rate on pasture (Carvalho et al, 2006;Silva et al, 2014). Use of forage grasses such as Tifton 85 (Cynodon spp.)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, concentrate supplementation may be necessary to meet the nutritional requirements of breeds specialized for meat production, such as Suffolk, allowing these animals to express their growth potential under grazing conditions. Studies performed in the Brazilian subtropical region showed that Suffolk lambs finished at 32-37 kg of body weight (BW) on Tifton 85 pasture presented an average daily gain of 135 -280 g day -1 in systems without weaning; 50 -110 g day -1 in systems with weaning and without supplementation; and around 150 g day -1 when they received concentrate supplementation post-weaning (Silva et al, 2014;Poli et al, 2020). In systems without weaning, the proteinenergy supplementation offered in creep feeding has been widely used to improve lambs' growth, resulting in…”
Section: Introductionmentioning
confidence: 99%